Level of knowledge and perceptions of basic life support among under graduate medical students in tertiary care teaching hospital in Central India. A questionnaire based study - Uike, Satyendra; Netty, Lokesh (Public Health Review: International Journal of Public Health Research, 2018)
Introduction: Knowledge of basic life support (BLS) is essential for medical personnel and for every person to save life in life threatening conditions. Well designed certified BLS /cardiopulmonary resuscitation (CPR) training workshop at a regular interval and compulsory training should be made as a part of present academic medical curriculum. Aim: To assess the present status knowledge and perception of CPR among clinical undergraduate medical students, a cross section questionnaire base study conducted to develop an efficacious training program in their academic curriculum. Results: We observed that the mean knowledge score of all students was less than 50%. Out of all, the mean knowledge score of female students was statistically significantly higher than the mean knowledge of male students, whereas intern students had higher knowledge score as compared to final and pre-final medical students. All the students possessed a positive perception of BLS. Conclusion: We concluded that knowledge about BLS among clinical undergraduates was below average, however, they have positive perceptions towards BLS. It can be improved by conducting well designed certified BLS /CPR training cum workshop.